The superconductivity of YBa2Cu3O7-δ reacted with nano-SiC - Wan Shaaidi, Wan Nurul Ain; Lim, Kean Pah; Matori, Khamirul Amin; Saion, Elias; Shaari, Abdul Halim; Chen, Soo Kien (Malaysian Solid State Science and Technology Society, 2014)
We report on the influence of nano-SiC as an additive on the superconductivity of polycrystalline YBa2Cu3O7-δ (YBCO) prepared via solid state reaction method. In particular, we studied the characteristic of superconducting transition temperature (Tc), crystal structure and microstructure of the YBCO system. X-ray diffraction patterns show the dominance of YBCO (123) phase in all the samples. The a and c axes increase slightly while the b-axis decreases with SiC addition causing the reduced orthorhombicity. Measurements of resistance versus temperature show that the normal state changes from metallic to semiconducting like behavior upon increasing the amount of additive from 1.5 wt.% onwards. The Tc-onset was found to decrease from 91 K for pure samples to 78 K for the 2 wt. % sample attributable to the adverse effect of Si. The broadening in superconducting transition breadth, ΔT indicates degraded crystallinity or inhomogeneity in the samples caused by SiC additions.